2000
DOI: 10.1007/s005950070043
|View full text |Cite
|
Sign up to set email alerts
|

The likely transformation of papillary thyroid carcinoma into anaplastic carcinoma during postoperative radioactive iodine-131 therapy: Report of a case

Abstract: We report herein a case of papillary carcinoma which appeared to transform into anaplastic carcinoma during postoperative radioactive iodine-131 (131I) therapy. A 67-year-old man who was diagnosed as having papillary thyroid carcinoma with bilateral neck lymph node involvement and multiple lung metastases underwent total thyroidectomy prior to 131I therapy. Immediately after a second course of 131I therapy, the patient complained of right neck pain and swelling, and a biopsy of the swollen neck lymph node was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…23,24 However, the transformation of differentiated carcinoma into ATC has been documented in patients following radioactive iodine therapy. 25,26 It seems in this case that irradiation may have contributed to the transformation or development of a poorly differentiated carcinoma that metastasized and transformed to an ATC.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 However, the transformation of differentiated carcinoma into ATC has been documented in patients following radioactive iodine therapy. 25,26 It seems in this case that irradiation may have contributed to the transformation or development of a poorly differentiated carcinoma that metastasized and transformed to an ATC.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the few cases where resection was performed, MNG and foci of papillary carcinoma were found on histologic examination in addition to ATC. 6 In some cases, ATC can be associated with the presence of low grade differentiated cancer in the thyroid, and it was reported that radiation therapy to the differentiated tumor plays a role in the transformation to an undifferentiated tumor. 5,7 In the few cases where ATC arose after radioactive iodine treatment for papillary carcinoma, p53 abnormalities were documented in both the primary tumor and ATC by immunohistochemical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In 20% of the cases a preexisting differentiated thyroid carcinoma is present, usually of the papillary type. 5,6 The pathogenesis of the aforementioned dedifferentiation from papillary carcinoma to ATC has been attributed in some cases to acquiring additional genetic changes that included the mutation in the p53 tumor suppressor gene. 6 In the few cases where resection was performed, MNG and foci of papillary carcinoma were found on histologic examination in addition to ATC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the p53 mutation is an excellent predictor of lymph node metastasis and capsular invasion of the tumor, and is a significant prognosticator of the survival outcome in patients with thyroid cancer (14). It (11,18,19) …”
Section: Rare (3) Whether the Solitary Metastasis In The Liver As Omentioning
confidence: 99%